Skills and knowledge of informatics, and training needs of hospital pharmacists in Thailand: A self-assessment survey. (October 2016) - Chonsilapawit, Teeraporn; Rungpragayphan, Suang
Highlights: Skills and knowledge of informatics, and training needs of hospital pharmacists in Thailand were assessed. Thai hospital pharmacists considered informatics highly necessary for their work. They believed that they were competent in basic computer and Internet skills. They realized their shortcomings in informatics knowledge/skills and needed more training. Abstract: Objective: Because hospital pharmacists have to deal with large amounts of health information and advanced information technology in practice, they must possess adequate skills and knowledge of informatics to operate efficiently. However, most current pharmacy curricula in Thailand barely address the principles and skills concerned with informatics, and Thai pharmacists usually acquire computer literacy and informatics skills through personal-interest training and self-study. In this study, we aimed to assess the skills and knowledge of informatics and the training needs of hospital pharmacists in Thailand, in order to improve curricular and professional development. Method: A self-assessment postal survey of 73 questions was developed and distributed to the pharmacy departments of 601 hospitals throughout the country. Practicing hospital pharmacists were requested to complete and return the survey voluntarily. Results: Within the 3 months of the survey period, a total of 805 out of 2002 surveys were returned. On average, respondents rated themselves as competent or better in the skills of basic computer operation, the Internet, information management, and communication. Understandably, they rated themselves at novice level for information technology and database design knowledge/skills, and at advanced beginner level for project, risk, and change management skills. Respondents believed that skills and knowledge of informatics were highly necessary for their work, and definitely needed training. Conclusion: Thai hospital pharmacists were confident in using computers and the Internet. They realized and appreciated their lack of informatics knowledge and skills, and needed more training. Pharmacy curricula and training should be developed accordingly.